2011
DOI: 10.1002/ejoc.201001725
|View full text |Cite
|
Sign up to set email alerts
|

DBU‐Promoted Nucleophilic Activation of Carbonic Acid Diesters

Abstract: The reactivity of carbonic acid diesters in the presence of the amidine base DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) has been investigated for the first time. Organic carbonates can be activated by DBU through the formation of N-alkoxycarbonyl ketene aminal 2 as the ultimate product. The latter species may form through deprotonation of the corresponding N-alkoxycarbonyl-amidinium cation 1 + by the amidine base. We have for the first time isolated and characterized,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 59 publications
(24 reference statements)
6
59
0
Order By: Relevance
“…It has been, in fact, reported that organic carbonates are activated by DBU via formation of an N -alkoxycarbonyl DBU derivative [6771]. However, in this case study, DBU most probably promotes the formation of the methoxycarbonyl reaction intermediate, as well as the intramolecular cyclisation reaction (B Al 2 mechanism).…”
Section: Reviewmentioning
confidence: 75%
“…It has been, in fact, reported that organic carbonates are activated by DBU via formation of an N -alkoxycarbonyl DBU derivative [6771]. However, in this case study, DBU most probably promotes the formation of the methoxycarbonyl reaction intermediate, as well as the intramolecular cyclisation reaction (B Al 2 mechanism).…”
Section: Reviewmentioning
confidence: 75%
“…Inspired by these works, we decided to explore the possibility of replacing the acyl halide, which is toxic and unstable, with 1-benzoylimidazole as the benzoylation reagent with 1,8-diazabicyclo-[5.4.0]undec-7-ene (DBU) as the catalyst. DBU is often used as a organobase catalyst in many base-catalyzed reactions [47][48][49][50], having been recognized as an excellent nucleophilic catalyst, leading to rapid and efficient acetylation of non-nucleophilic azacycles, such as indoles, pyrroles, and oxazolidinones. D-pyranosides.…”
Section: Resultsmentioning
confidence: 99%
“…7, 11 Shieh’s work led Carafa and colleagues to shore up DBU’s catalytic nature in 2011, in which they isolated the unprecedented ketene aminal. 12 Carafa’s findings significantly influenced the proposed reaction scheme in this work; specifically, it was their isolation of the ketene aminal species and their emphasis on the ketene aminal as the key intermediate in acylation reactions. In 2012, Waymouth/Hedrick et al showed the potential for DBU to catalyze the polymerization of lactide in the absence of an alcohol macro-initiator involving a hypothesized zwitterionic ROP (ZROP) mechanism.…”
Section: Introductionmentioning
confidence: 92%